First-Principles Calculations of Thermoelectric Properties of IV–VI Chalcogenides 2D Materials - Morales-Ferreiro, J. O.; Diaz-Droguett, D. E.; Celentano, D.; Luo, T. (Frontiers in Mechanical Engineering, 2017)
A first-principles study using density functional theory and Boltzmann transport theory has been performed to evaluate the thermoelectric (TE) properties of a series of single-layer 2D materials. The compounds studied are SnSe, SnS, GeS, GeSe, SnSe2, and SnS2, all of which belong to the IV–VI chalcogenides family. The first four compounds have orthorhombic crystal structures, and the last two have hexagonal crystal structures. Solving a semi-empirical Boltzmann transport model through the BoltzTraP software, we compute the electrical properties, including Seebeck coefficient, electrical conductivity, power factor, and the electronic thermal conductivity, at three doping levels corresponding to 300 K carrier concentrations of 1018, 1019, and 1020 cm−3. The spin orbit coupling effect on these properties is evaluated and is found not to influence the results significantly. First-principles lattice dynamics combined with the iterative solution of phonon Boltzmann transport equations are used to compute the lattice thermal conductivity of these materials. It is found that these materials have narrow band gaps in the range of 0.75–1.58 eV. Based on the highest values of figure-of-merit ZT of all the materials studied, we notice that the best TE material at the temperature range studied here (300–800 K) is SnSe.